An analysis of FDI: linkages and local firms capability (a case of manufacturing sector in Melaka) / Prof. Madya Dr. Abdul Halim Mohd Noor, Rosfadzimi Mat Saad and Mohd Saladin Abd Rasool - Mohd Noor, Prof. Madya Dr. Abdul Halim; Mat Saad, Rosfadzimi; Abd Rasool, Mohd Saladin (Institute of Research, Development and Commercialization (IRDC), 2004)
One key element for firms especially the small and medium enterprises (SMEs) to increase their competitiveness is the ability to form linkages with other firms either vertically or horizontally. This paper is based on a data set of forty foreign manufacturing firms operating in industrial estates in Malacca. The data provide statistical information such as firm's profile, production capability, nature of technology employed, and linkages developed. Linkages occur whenever any particular firms affects the amount and/or conditions of supply of, or demand for, other goods and services by another firm. It is commonly used to gauge the capability for firms to compete which is regarded as vital today with the advent of globalization and trade liberalization as domestic firms in industrializing countries face a daunting task in meeting head on with their global competitors. This paper assesses the two main types of linkages, namely developmental linkages and dependent linkages which are used by economist to proxy the level of competitiveness and capability of firms. Specifically, this study would like to explore the developmental linkages which is essential in developing the basic platform of a long term relationship between foreign multinationals with local suppliers. Using variables such as source of technology as a proxy to the level of linkages and independent variables such as exports value, research and development (R & D) expenditure, number of workers, years in operation and government incentives received, the study utilizes the simple regression analysis using ordinary least square (OLS) method to estimate the coefficients. This study found evidence that presence of foreign firms have a positive impact on local SMEs' performance. Increasing number of technical staff and increasing involvement of local partners and firms were among the significant variables employed to explain the reasons why firms source local components with higher technical requirements (as compared to local raw materials).